Characterization of an EcoR124I restriction-modification enzyme produced from a deleted form of the DNA-binding subunit, which results in a novel DNA specificity - Abadjieva, A; Scarlett, G; Janscák, P; Dutta, C F; Firman, K (Folia microbiologica, 2003)
We purified and characterized both the methyltransferase and the endonuclease containing the HsdS delta 50 subunit (type I restriction endonucleases are composed of three subunits--HsdR required for restriction, HsdM required for methylation and HsdS responsible for DNA recognition) produced from the deletion mutation hsdS delta 50 of the type IC R-M system EcoR 124I; this mutant subunit lacks the C-terminal 163 residues of HsdS and produces a novel DNA specificity. Analysis of the purified HsDs delta 50 subunit indicated that during purification it is subject to partial proteolysis resulting in removal of approximately 1 kDa of the polypeptide at the C-terminus. This proteolysis prevented the purification of further deletion mutants, which were determined as having a novel DNA specificity in vivo. After biochemical characterization of the mutant DNA methyltransferase (MTase) and restriction endonuclease we found only one difference comparing with the wild-type enzyme--a significantly higher binding affinity of the MTase for the two substrates of hemimethylated and fully methylated DNA. This indicates that MTase delta 50 is less able to discriminate the methylation status of the DNA during its binding. However, the mutant MTase still preferred hemimethylated DNA as the substrate for methylation. We fused the hsdM and hsdS delta 50 genes and showed that the HsdM-HsdS delta 50 fusion protein is capable of dimerization confirming the model for assembly of this deletion mutant.
Keywords: proteiny z Escherichia coli; DNA restrikčně-modifikační enzymy; DNA-Binding Proteins; sekvence nukleotidů; Substrate Specificity; DNA vazebné proteiny; Molecular Sequence Data; Electrophoretic Mobility Shift Assay; molekulární sekvence - údaje; mutace; Recombinant Proteins; Escherichia coli Proteins; bakteriální proteiny; retardační test; DNA; Amino Acid Sequence; rekombinantní proteiny; DNA Methylation; metylace DNA; Base Sequence; Deoxyribonucleases, Type I Site-Specific; substrátová specifita; Bacterial Proteins; Mutation; DNA Restriction-Modification Enzymes; restrikční endonukleasy typu I; sekvence aminokyselin